The difficult legacy of mining in past and contemporary Potosí and Ouro Preto - De Souza Santos, A; Iamamoto, S (University of Texas Press, 2019)
The cities of Potosí (Bolivia) and Ouro Preto (Brazil) have played central economic roles during Latin America’s long colonial history of mineral extraction, feeding the Spanish and Portuguese empires with silver (Potosí) and gold (Ouro Preto) and, consequently, changing the world’s economy. Based on ethnography, interviews and archival research, in this article we argue that mining in these cities should be understood through the frame of a “difficult heritage” (Macdonald, 2009), incorporating mining’s social and environmental atrocities in the official representations of their pasts. We first analyze how the colonial period was depicted in contemporary heritage policies and the role it played in fostering nationalism both in Bolivia and Brazil. Then, we explore how two main issues were excluded from the official narratives but remained represented in urban spaces and in local inhabitants’ perceptions of them: the environmental impact directly or indirectly caused by mining and the racist violence imposed on African and indigenous peoples to guarantee mass labour for mining enterprises. Today, as contemporary Latin American societies are struggling to reinvent their national selves without reproducing long-standing patterns of race inequalities and extractivism, accounting for the complexity of colonial mining heritage becomes increasingly relevant.